Damage in cohesive granular materials: simulations and geophysical implications - Canel, Vincent; Campillo, Michel; Jia, Xiaoping; Ionescu, Ioan R. (Comptes Rendus. Géoscience)
The aim of this paper is to test a simple damage model of a cohesive granular medium to study the relationship between the damage and velocity of elastic waves. Our numerical experiments of edometric compression show that the microscopic deformation quickly becomes very heterogeneous, while our simulations of elastic waves propagation show that a small amount of damage induces a dramatic decrease in the elastic velocity. This shows that cohesive discrete media are very sensitive to strain field heterogeneity, and that the wave velocities in these media can measure subtle transient deformation processes, such as earthquake initiation phases.